Surface glaze-sealed hollow glass beads, preparation method thereof, high-temperature high-strength low-density cement paste and application

The hollow glass microbeads are sealed with surface glaze to form a temperature-resistant and corrosion-resistant enamel layer, which solves the problem of poor structural stability of traditional hollow glass microbeads under high temperature conditions, significantly improves the high-temperature compressive strength of the low-density cementing system, and meets the technical needs of deep well ultra-deep well cementing operations.

CN119683888AActive Publication Date: 2025-03-25CHINA NAT PETROLEUM CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411653244.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-25
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

During the drilling and completion of deep well ultra-deep wells, the formation has low pressure bearing capacity and easy leakage, and the cement slurry return and sealing quality are difficult to ensure. The structural stability of traditional hollow glass microbeads is poor under high temperature conditions, resulting in slow development of high-temperature strength, low numerical values ​​and obvious attenuation of low-density cement slurry systems.

Method used

Hollow glass microbeads are sealed with surface glaze, and the surface of hollow glass microbeads is grafted by silane coupling agent and chelating group-containing active monomers on the surface, combining nano-scale glaze sealing materials and small-molecular organic acid salts to form a temperature-resistant and corrosion-resistant enamel layer to improve the mechanical properties and stability of the microbeads.

Benefits of technology

The high-temperature compressive strength of the low-density cement slurry system is significantly improved, the density can be adjusted within the range of 1.30~1.50g/cm3, the high-temperature compressive strength of 180℃ for 24 hours is greater than 18MPa, and the compressive strength of 48 hours is greater than 25MPa, reducing the risk of well leakage during cementing construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683888A_ABST
    Figure CN119683888A_ABST
Patent Text Reader

Abstract

The invention discloses a surface glaze-sealed hollow glass bead and a preparation method thereof, high-temperature high-strength low-density cement paste and application, the preparation method comprises the following steps: adding hollow glass beads into an absolute ethyl alcohol solution, dropwise adding a silane coupling agent, separating, leaching and drying to obtain hollow glass beads with surfaces grafted with the silane coupling agent; adding the hollow glass beads of which the surfaces are grafted with the silane coupling agent and active monomers containing chelating groups into deionized water, mixing, adding an initiator for reaction, adding a polymerization inhibitor, and washing and drying to prepare hollow glass beads of which the surfaces are grafted with the chelating groups; adding a first suspension stabilizer, a nanoscale glaze sealing material and an auxiliary agent into deionized water, and uniformly stirring to prepare glaze sealing slurry; and spraying glaze sealing slurry on the hollow glass beads with the surfaces grafted with the chelating groups, drying in vacuum, and firing to obtain the hollow glass beads with the surfaces being glazed and sealed. The surface glaze-sealed hollow glass bead improves the capability of resisting erosion of high-alkalinity substances in cement paste and keeping structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of well drilling, completion and cementing, and in particular to a surface glaze-sealed hollow glass microsphere and a preparation method thereof, and a high-temperature, high-strength and low-density cement slurry and application thereof. Background Art

[0002] With the gradual deepening of deep formation exploration and development and the continuous improvement of petroleum technology, the number of deep and ultra-deep wells has increased rapidly, and the drilling capacity has exceeded 9,000 meters and reached a new level of 10,000 meters. However, in the process of drilling and completion of deep and ultra-deep wells, most of them have complex problems such as low formation pressure bearing capacity, easy leakage, narrow safety density window, limited injection and displacement, and it is difficult to ensure the return height of cement slurry and the quality of sealing. In addition, under high temperature conditions, the hydration rate of oil well cement is fast, the pH value is high, and the hydration products are significantly different from those at low temperature, which has a great impact on cementing cement slurry admixtures and admixtures. The traditional lightening agent, hollow glass microspheres, is easily affected by high temperature (greater than 150°C) conditions and differences in the physical and chemical properties of silicate cement. The macroscopic structure shows volume expansion and contraction, and the microscopic morphology shows erosion and dissolution of the skeleton structure, resulting in the low-density cement slurry system. The high-temperature strength develops slowly, the value is low, and the attenuation is obvious. It is not conducive to ensuring the integrity of the cement ring, and restricts the simplification of the wellbore structure and the implementation of subsequent operations such as fracturing and acidizing.

[0003] In summary, there are still certain deficiencies and room for improvement when using the existing conventional glass bead low-density cement slurry system to carry out cementing operations under complex conditions such as deep wells, ultra-deep wells, low-pressure and leaky layers. It is urgent to improve the mechanical properties of the low-density cement slurry system while ensuring the construction properties such as slurry thickening, rheology and stability, so as to provide technical support for the exploration and development of deep oil and gas resources. Summary of the invention

[0004] In order to reduce the surface defects of glass microsphere lighteners, improve their ability to resist corrosion by highly alkaline substances in cement slurry and maintain structural stability, and reduce the risk of cracks and peeling between the cement matrix, and improve the lighteners used for cementing in deep low-pressure leaky layers and high-temperature working conditions, so that the cementing cement slurry has high-temperature resistance and high-strength mechanical properties, the present invention provides a surface glaze-sealed hollow glass microsphere and its preparation method, high-temperature, high-strength, low-density cement slurry and its application.

[0005] In a first aspect, an embodiment of the present invention provides a method for preparing a surface glaze-sealed hollow glass microsphere, wherein the raw material composition of the surface glaze-sealed hollow glass microsphere comprises, by weight: 36.5 to 40.5 parts of hollow glass microspheres, 2.9 to 3.3 parts of silane coupling agents, 9.2 to 11 parts of active monomers containing chelating groups, 44.8 to 50.3 parts of nano-scale glaze-sealed materials, 0.9 to 1 parts of auxiliary agents, and 1.3 to 1.5 parts of first suspension stabilizers;

[0006] The preparation method may include:

[0007] The hollow glass microspheres are added into an anhydrous ethanol solution, and a silane coupling agent is added dropwise, and the solution is separated, rinsed, and dried to obtain hollow glass microspheres with the silane coupling agent grafted on the surface;

[0008] The hollow glass microspheres with silane coupling agent grafted on the surface and the active monomer containing chelate group are added into deionized water for mixing, an initiator is added for reaction, an inhibitor is added, and the hollow glass microspheres with chelate group grafted on the surface are prepared after washing and drying;

[0009] Adding the first suspension stabilizer, the nano-scale glaze sealing material and the auxiliary agent into deionized water, and stirring evenly to prepare a glaze sealing slurry;

[0010] The hollow glass microbeads with chelating groups grafted on the surface are sprayed with glaze slurry, vacuum dried and fired to obtain the hollow glass microbeads with glaze sealing on the surface.

[0011] In one embodiment, the hollow glass microspheres have a compressive strength of 12000 psi.

[0012] In one embodiment, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.

[0013] In one embodiment, the active monomer containing a chelating group is itaconic acid and / or fumaric acid.

[0014] In one embodiment, the nano-scale glaze sealing material includes, by mass, 16.7 to 33.3 parts of 300 to 500 nm nano-dolomite, 25 to 33.3 parts of 100 to 500 nm nano-zircon powder, 15.4 to 33.3 parts of 400 to 1000 nm nano-sodium potassium stone powder, and 16.7 to 23.1 parts of 50 to 300 nm nano-strontium carbonate powder.

[0015] In one embodiment, the auxiliary agent is at least one of the following: sodium tripolyphosphate, sodium tetraphosphate, and sodium tannate.

[0016] In one embodiment, the first suspension stabilizer is bentonite and / or china clay.

[0017] In one embodiment, the preparation method may specifically include:

[0018] The hollow glass microspheres are added to an anhydrous ethanol solution, and a silane coupling agent is added dropwise at 60 to 70° C. within 1 hour; then cooled to room temperature, separated by a high-speed centrifuge, and the separated product is washed with deionized water until it is neutral, and dried to obtain hollow glass microspheres with a silane coupling agent grafted on the surface;

[0019] The hollow glass microspheres with surface grafted silane coupling agent and active monomers containing chelating groups are added to deionized water, mixed, stirred evenly, adjusted to a neutral pH value, and supplemented with deionized water to make the solid content in the suspension reach 15wt%; a protective gas is introduced, the temperature is raised to 50°C, an initiator is added to react, and the reaction is stirred for 6 to 8 hours at a temperature preservation temperature; the protective gas is turned off, an inhibitor is added, stirred, cooled to room temperature, washed with clean water, and spray-dried to obtain hollow glass microspheres with surface grafted chelating groups;

[0020] The first suspension stabilizer, the nano-scale glaze sealing material and the auxiliary agent are added into deionized water, the deionized water is supplemented so that the content of the nano-scale glaze sealing material in the suspension reaches 70wt%, and the glaze sealing slurry is prepared by stirring evenly;

[0021] The sealing glaze slurry is sprayed evenly onto the hollow glass microspheres with chelating groups grafted on the surface by a spraying method; dried in a vacuum oven at 60°C for 1 day, dried at 110°C for 2 days, and sieved; fired in a high-temperature electric furnace at 800-1200°C for 8-10 hours, cooled and sieved to obtain a powder material as the surface glaze sealing hollow glass microspheres.

[0022] In a second aspect, an embodiment of the present invention provides a surface glaze-sealed hollow glass microsphere, which is prepared according to the preparation method of the surface glaze-sealed hollow glass microsphere described in the first aspect.

[0023] In the third aspect, an embodiment of the present invention provides a high-temperature, high-strength, low-density cement slurry. The raw material composition of the high-strength, low-density cement slurry includes, by mass: 100 parts of G-grade oil well cement, 29 to 60 parts of the surface glaze hollow glass beads described in the second aspect, 15 parts of high-temperature strength decay material, 4 parts of high-temperature anti-cracking material, 2 to 3 parts of a second suspension stabilizer, 1.2 to 2 parts of a dispersant, 4.3 to 5 parts of a high-temperature fluid loss reducer, 2 to 2.5 parts of a high-temperature retarder, 1 part of a defoaming agent, and 67 to 80 parts of tap water.

[0024] In one embodiment, the high temperature strength decay material is compounded by 325 mesh composite silicon micropowder and 1500 mesh crystalline silicon micropowder in a mass ratio of 5:1.

[0025] In one embodiment, the high temperature anti-cracking material includes, by mass, 10 parts of 1-3 mm calcium sulfate whiskers, 30 parts of 2-4 mm basalt fibers, 20 parts of 1-3 mm aluminum oxide whiskers, and 40 parts of styrene-butadiene rubber powder.

[0026] In a fourth aspect, an embodiment of the present invention provides an application of the high-temperature, high-strength, low-density cement slurry described in the third aspect in well completion and cementing.

[0027] The beneficial effects of the above technical solution provided by the embodiment of the present invention include at least:

[0028] The embodiment of the present invention provides a surface glaze-sealed hollow glass microsphere and its preparation method, high-temperature, high-strength, low-density cement slurry and application. The surface glaze-sealed hollow glass microsphere is a lightening agent, and the density of the cement slurry is adjusted by utilizing its hollow and low-density characteristics; a silane coupling agent is used to graft a molecular chain rich in adsorption groups (-COOH) on the surface of the hollow glass microsphere, and the adhesion effect of the glaze slurry on the surface of the hollow glass microsphere is improved through the adsorption and chelation between -COOH and heavy metal ions in nano inorganic mineral powder; a small molecule organic acid salt is used as an auxiliary agent to assist the uniform coating and deep penetration of the glaze material on the surface of the hollow glass microsphere. On this basis, through variable temperature continuous drying, the glaze slurry on the surface of the hollow glass microsphere is prevented from cracking due to the rapid escape of water or uneven escape rate; and then through low-temperature firing, a hollow glass microsphere with a layer of heat-resistant and corrosion-resistant enamel layer on the surface is finally obtained, thereby improving its macroscopic mechanical properties and the ability to resist corrosion by cement hydration products, formation fluids, etc., and improving the structural integrity and compressive strength of low-density cement stone under high-temperature working conditions at the bottom of the well.

[0029] High temperature, high strength and low density cement slurry with adjustable density (1.30~1.50g / cm 3 ), 180℃ high temperature 24h compressive strength greater than 18MPa, 48h compressive strength greater than 25MPa, low API water loss, good rheological properties, free liquid is 0, density difference less than 0.05g / cm 3 It provides strong technical support to reduce the risk of leakage during cementing construction and ensure the exploration and development benefits of difficult-to-use reserves and unconventional oil and gas resources in complex deep wells and ultra-deep wells.

[0030] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the written description and the accompanying drawings.

[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0033] Figure 1 This is a thickening curve diagram provided in Example 1 of the present invention;

[0034] Figure 2 This is a thickening curve diagram provided in Example 2 of the present invention;

[0035] Figure 3 This is a thickening curve diagram provided in Example 3 of the present invention;

[0036] Figure 4 This is a thickening curve diagram provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0038] In view of the fact that the existing conventional glass bead low-density cement slurry system still has certain shortcomings and room for improvement when carrying out cementing operations under complex conditions such as deep wells, ultra-deep wells, low-pressure and leaky layers, and the technical problem of being unable to improve the mechanical properties of the low-density cement slurry system while ensuring the construction properties such as slurry thickening, rheology and stability, the present invention is proposed to provide a surface glaze-sealed hollow glass microsphere and its preparation method, high-temperature and high-strength low-density cement slurry and application that overcome the above problems or at least partially solve the above problems.

[0039] Description of raw materials for the examples and comparative examples of the present invention:

[0040] Hollow glass microspheres, commercially available, with a compressive strength of 12000 psi.

[0041] The silane coupling agent is γ-methacryloxypropyltrimethoxysilane (KH-570), which is chemically pure and commercially available.

[0042] The active monomer containing the chelating group is one or both of itaconic acid (IA) and fumaric acid (FA), which are chemically pure and commercially available.

[0043] The nano-grade glaze sealing material includes, by mass, 16.7 to 33.3 parts of 300-500nm nano-dolomite, 25 to 33.3 parts of 100-500nm nano-zircon powder, 15.4 to 33.3 parts of 400-1000nm nano-sodium potassium stone powder, and 16.7 to 23.1 parts of 50-300nm nano-strontium carbonate powder. It is industrial grade and commercially available.

[0044] The auxiliary agent is one or more of sodium tripolyphosphate, sodium tetraphosphate and sodium tannate, which are industrial grade and commercially available.

[0045] The suspension stabilizer is bentonite or china clay, industrial grade, commercially available.

[0046] Sodium hydroxide (NaOH) solution (concentration 30wt%) and dilute hydrochloric acid solution (concentration 4mol / L) are used as pH adjusters, which are chemically pure and commercially available; the protective gas during the polymerization reaction is high-purity argon (Ar), industrial grade, commercially available; the solvents used are deionized water and anhydrous ethanol, which are analytically pure and commercially available.

[0047] G-grade oil well cement, high sulfate resistance (HSR), Jiahua Special Cement Co., Ltd.; high temperature strength anti-decay material, made of 325 mesh composite silica powder and 1500 mesh crystalline silica powder in a mass ratio of 5:1, Hongrun Quartz Silica Powder Co., Ltd.

[0048] The dispersant is a commercially available ketone-aldehyde oil well cement dispersant.

[0049] The high-temperature anti-cracking material is composed of commercially available inorganic chopped fibers and polymer resins. The specific proportions are as follows by weight: calcium sulfate whiskers (1-3 mm) are 10%, basalt fibers (2-4 mm) are 30%, alumina whiskers (1-3 mm) are 20%, and styrene-butadiene rubber powder (50-100 um) is 40%. The above materials are weighed in proportion, stirred evenly, and packaged for later use.

[0050] The defoaming agent is one of commercially available tributyl phosphate, polyoxypropylene glycerol, and polydimethylsiloxane.

[0051] The fluid loss agent is homemade according to Example 5 in the patent application number 202010137114.6.

[0052] The retarder is self-made according to the patent application number 201610539424.4.

[0053] The second suspension stabilizer is a weak gel polymer, which is self-made by Example 2 in the patent application number 202110009555.2.

[0054] It should also be noted that the experimental methods in the following examples without specifying specific conditions are based on conventional methods and conditions. The raw materials in the following examples without specifying specific manufacturers and product numbers are all purchased from conventional markets.

[0055] Example 1

[0056] (1) Pretreatment of hollow glass microspheres

[0057] 40.5 parts of hollow glass microspheres were added to 150 parts of anhydrous ethanol solution, stirred at 150 r / min for 30 minutes, and 3.3 parts of KH570 were added dropwise at 60°C within 1 hour; then cooled to room temperature, separated by a high-speed centrifuge, and the separated material was rinsed with deionized water until it was neutral, and dried to obtain hollow glass microspheres with surface grafted silane coupling agent for use.

[0058] The hollow glass microspheres with surface grafted silane coupling agent and 11 parts of IA are added into deionized water and mixed, and stirred evenly at 120r / min; the pH value of the suspension is adjusted to 7; deionized water is added to make the solid content of the suspension reach 15wt%; Ar is introduced, and the temperature is raised to 50°C; APS is added, and the temperature is kept and stirred for 6h; Ar is turned off, PBQ is added, and stirring is continued for 20min; cooling, washing with clean water, and spray drying are performed to obtain hollow glass microspheres with surface grafted chelating groups.

[0059] (2) Preparation of glaze slurry

[0060] Weigh a certain mass of deionized water and 1.3 parts of bentonite, and stir them at 300r / min; weigh 44.8 parts of glaze sealing materials, of which 33.3% are nano-dolomite powder, 25% are nano-zircon powder, 25% are nano-sodium potassium stone powder, and 16.7% are nano-strontium carbonate powder, and stir them at 1500r / min; weigh 0.9 parts of sodium tripolyphosphate, and stir them at 1500r / min; add deionized water so that the content of nano-scale glaze sealing materials in the suspension reaches 70wt%, and stir them at 1500r / min to obtain glaze sealing slurry.

[0061] (3) Preparation of hollow glass microspheres with surface glaze

[0062] ①Use the spraying method to evenly spray the prepared glaze slurry onto the pre-treated hollow glass beads to ensure that the glaze slurry is fully infiltrated and wrapped on the surface of the hollow glass beads.

[0063] ② Move the hollow glass microspheres with the sealing glaze slurry into a vacuum oven, dry at 60°C for 1 day, dry at 110°C for 2 days, and sieve; put into a high-temperature electric furnace, and burn at 1200°C for 8 hours; cool and sieve to obtain the powder material, which is the surface glaze sealing hollow glass microspheres (A).

[0064] Step 2: Preparation of high temperature, high strength and low density cement slurry

[0065] The cement slurry formula is as follows in parts by mass: 100 parts of G-grade oil well cement, 60 parts of surface glaze sealing hollow glass beads (A), 15 parts of high-temperature strength anti-decay material, 4 parts of high-temperature anti-cracking material, 2 parts of dispersant, 3 parts of second suspension stabilizer, 5 parts of high-temperature fluid loss reducer, 2 parts of high-temperature retarder, 1 part of defoaming agent, and 80 parts of tap water.

[0066] Weigh oil well cement, surface glaze hollow glass microspheres, high temperature strength anti-decay material, high temperature anti-cracking material and dispersant in proportion and mix evenly to obtain a dry mix; mix high temperature retarder, high temperature fluid loss reducer, suspension stabilizer, defoamer and tap water evenly to obtain a wet mix; at a speed of 4000±200r / min, introduce the dry mix evenly into the wet mix, and after the dry mix is ​​completely wetted, continue stirring for 35s to obtain a high temperature, high strength and low density cement slurry.

[0067] The density of cement slurry is 1.30×10 3 kg / m 3 , the experimental results are shown in Appendix 1.

[0068] Example 2

[0069] The first step is the preparation of hollow glass microspheres with surface glaze

[0070] (1) Pretreatment of hollow glass microspheres

[0071] 38.7 parts of hollow glass microspheres were added to 150 parts of anhydrous ethanol solution, and stirred at 150 r / min for 30 minutes; 3.1 parts of KH570 were added dropwise at 60°C within 1 hour; then cooled to room temperature, separated by a high-speed centrifuge, and the separated material was rinsed with deionized water until it was neutral, and dried to obtain hollow glass microspheres with surface grafted silane coupling agent for use.

[0072] The hollow glass microspheres with surface grafted silane coupling agent and 10.8 parts of FA are added into a certain amount of deionized water, mixed, and stirred evenly at 120r / min; the pH value of the suspension is adjusted to 7; deionized water is added to make the solid content of the suspension reach 15wt%; Ar is introduced, and the temperature is raised to 50°C; APS is added, and the temperature is kept, stirred, and reacted for 6h; Ar is turned off, PBQ is added, and stirring is continued for 20min; cooling, washing with clean water, and spray drying are obtained to obtain hollow glass microspheres with surface grafted chelating groups.

[0073] (2) Preparation of glaze slurry

[0074] Weigh a certain mass of deionized water and 1.3 parts of porcelain clay, and stir them at 300r / min; weigh 46.5 parts of glaze sealing materials, of which 30.8% are nano-dolomite powder, 30.8% are nano-zircon powder, 15.4% are nano-sodium potassium stone powder, and 23% are nano-strontium carbonate powder, and stir them at 1500r / min; weigh 0.95 parts of sodium tannate, and stir them at 1500r / min; add deionized water so that the content of nano-scale glaze sealing materials in the suspension reaches 70wt%, and stir them at 1500r / min to obtain glaze sealing slurry.

[0075] (3) Preparation of hollow glass microspheres with surface glaze

[0076] ①Use the spraying method to evenly spray the prepared glaze slurry onto the pre-treated hollow glass beads to ensure that the glaze slurry is fully infiltrated and wrapped on the surface of the hollow glass beads.

[0077] ② Move the hollow glass microspheres with the sealing glaze slurry into a vacuum oven, dry at 60°C for 1 day, dry at 110°C for 2 days, and sieve; put into a high-temperature electric furnace, and burn at 1000°C for 8 hours; cool and sieve to obtain the powder material, which is the surface glaze sealing hollow glass microspheres (B).

[0078] The second step is the preparation of high temperature resistant, high strength and low density cement slurry system

[0079] The cement slurry formula is as follows by mass: 100 parts of G-grade oil well cement, 40 parts of surface glaze hollow glass microspheres (B), 15 parts of high temperature strength anti-decay material, 4 parts of high temperature anti-cracking material, 1.5 parts of dispersant, 2 parts of second suspension stabilizer, 5 parts of high temperature fluid loss reducer, 2.2 parts of high temperature retarder, 1 part of defoamer, and 73 parts of tap water. The preparation process of the high temperature, high strength and low density cement slurry in Example 2 of the present invention refers to the above Example 1.

[0080] The density of cement slurry is 1.40×10 3 kg / m 3 , the experimental results are shown in Appendix 1.

[0081] Example 3

[0082] The first step is the preparation of hollow glass microspheres with surface glaze

[0083] (1) Pretreatment of hollow glass microspheres

[0084] 36.5 parts of hollow glass microspheres were added to 145 parts of anhydrous ethanol solution, stirred at 150 r / min for 30 minutes, and 2.9 parts of KH570 were added dropwise at 60°C within 1 hour; then cooled to room temperature, separated by a high-speed centrifuge, and the separated material was rinsed with deionized water until it was neutral, and dried to obtain hollow glass microspheres with surface grafted silane coupling agent for use.

[0085] The hollow glass microspheres with surface grafted silane coupling agent, 5 parts of IA and 4.2 parts of FA are added into a certain amount of deionized water, mixed, and stirred evenly at 120r / min; the pH value of the suspension is adjusted to 7; deionized water is added to make the solid content of the suspension reach 15wt%; Ar is introduced, and the temperature is raised to 50°C; APS is added, and the temperature is kept and stirred for 6 hours; Ar is turned off, PBQ is added, and stirring is continued for 20 minutes; cooling, washing with clean water, and spray drying are obtained to obtain hollow glass microspheres with surface grafted chelating groups.

[0086] (2) Preparation of glaze slurry

[0087] Weigh a certain mass of deionized water and 1.5 parts of porcelain clay, and stir them at 300r / min; weigh 50.3 parts of glaze sealing materials, of which 16.7% are nano-dolomite powder, 33.3% are nano-zircon powder, 33.3% are nano-sodium potassium powder, and 16.7% are nano-strontium carbonate powder, and stir them at 1500r / min; weigh 1 part of sodium tetraphosphate, and stir them at 1500r / min; add deionized water so that the content of nano-scale glaze sealing materials in the suspension reaches 70wt%, and stir them at 1500r / min to obtain glaze sealing slurry.

[0088] (3) Preparation of hollow glass microspheres with surface glaze

[0089] ①Use the spraying method to evenly spray the prepared glaze slurry onto the pre-treated hollow glass beads to ensure that the glaze slurry is fully infiltrated and wrapped on the surface of the hollow glass beads.

[0090] ② Move the hollow glass microspheres with the sealing glaze slurry into a vacuum oven, dry at 60°C for 1 day, dry at 110°C for 2 days, and sieve; put into a high-temperature electric furnace, and burn at 1000°C for 10 hours; cool, sieve, and the obtained powder material is the surface glaze sealing hollow glass microspheres (C).

[0091] Step 2: Preparation of high temperature, high strength and low density cement slurry

[0092] The cement slurry formula is as follows by weight percentage: 100 parts of G-grade oil well cement, 29 parts of surface glaze hollow glass microspheres (C), 15 parts of high temperature strength anti-decay material, 4 parts of high temperature anti-cracking material, 1.2 parts of dispersant, 2 parts of suspension stabilizer, 4.3 parts of high temperature fluid loss reducer, 2.5 parts of high temperature retarder, 1 part of defoamer, and 67 parts of tap water. The preparation process of the high temperature, high strength and low density cement slurry in Example 3 of the present invention refers to the above Example 1.

[0093] The density of cement slurry is 1.50×10 3 kg / m 3 , the experimental results are shown in Appendix 1.

[0094] Comparative Example 1

[0095] Commercially available hollow glass microspheres (D).

[0096] The cement slurry formula is as follows in parts by mass: 100 parts of G-grade oil well cement, 40 parts of hollow glass microspheres, 15 parts of high-temperature strength anti-decay material, 4 parts of high-temperature anti-cracking material, 2 parts of dispersant, 3 parts of second suspension stabilizer, 5 parts of high-temperature fluid loss reducer, 2 parts of high-temperature retarder, 1 part of defoaming agent, and 72 parts of tap water.

[0097] The density of cement slurry is 1.30×10 3 kg / m 3, the experimental results are shown in Appendix 1.

[0098] Comparative Example 2

[0099] Commercially available hollow glass microspheres (D).

[0100] The cement slurry formula is as follows by weight percentage: 100 parts of oil well cement, 28 parts of hollow glass microspheres, 15 parts of high-temperature strength anti-decay material, 4 parts of high-temperature anti-cracking material, 1.5 parts of dispersant, 2 parts of second suspension stabilizer, 5 parts of high-temperature fluid loss reducer, 2 parts of high-temperature retarder, 1 part of defoaming agent, and 66 parts of tap water.

[0101] The density of cement slurry is 1.40×10 3 kg / m 3 , the experimental results are shown in Appendix 1.

[0102] Comparative Example 3

[0103] Commercially available hollow glass microspheres (D).

[0104] The cement slurry formula is as follows by weight percentage: 100 parts of oil well cement, 19 parts of hollow glass microspheres, 15 parts of high-temperature strength anti-decay material, 4 parts of high-temperature anti-cracking material, 1.5 parts of dispersant, 2 parts of second suspension stabilizer, 4.3 parts of high-temperature fluid loss reducer, 2 parts of high-temperature retarder, 1 part of defoaming agent, and 61 parts of tap water.

[0105] The density of cement slurry is 1.50×10 3 kg / m 3 , the experimental results are shown in Appendix 1.

[0106] The experiment was carried out in accordance with the national standard GB / T 19139-2012 "Test Methods for Oil Well Cement" to evaluate the compressive strength, thickening, water loss, free liquid, density difference, rheology and other properties of the high-strength and low-density cement slurry system of the present invention.

[0107] The main experimental instruments are: 30-60 type wall-edge agitator, 8240 type high temperature and high pressure thickener, 7357 type high temperature and high pressure curing kettle, products of CHANDLER Company of the United States; 35SA type rotational viscometer, Fann Company of the United States; HH-420 type constant temperature digital display water tank, Changzhou Yineng Experimental Instrument Factory.

[0108] Table 1 Various properties test table of cement slurry system of embodiment and comparative example

[0109]

[0110]

[0111] From the data in Table 1, we can see that the high-temperature, high-strength, low-density cement slurry system prepared based on glaze-sealed hollow glass microspheres has a density of 1.30-1.50 g / cm 3 The range is adjusted according to the construction needs, and the fluidity is greater than 20cm; when the circulation temperature is 160℃, the initial viscosity of Example 1 is 15Bc, and the thickening time is 309min ( Figure 1 ), Example 2 initial thickening 17Bc, thickening time 300min ( Figure 2 ), Example 3 initial thickening 13Bc, thickening time 317min ( Figure 3 ), the thickening curves of all examples are normal, without abnormal gelation such as "heart-wrapping"; under the experimental conditions of 93℃×6.9MPa, the water loss of Example 1 Q 30 92mL, Example 2 water loss Q 30 56mL, Example 3 water loss Q 30 The volume of the sample was 44 mL, and no gas penetration occurred during the experiment. At the same time, the rheological parameters of each embodiment were n>0.80, k≤0.76 Pa.s n .

[0112] The sedimentation stability evaluation shows that the difference in density between the upper and lower cement slurry after standing at 93°C for 2 hours with a 3% addition of the suspension stabilizer in Example 1 is 0.02 g / cm 3 After standing at 180℃ for 24 hours, the upper and lower density difference of cement paste was 0.038g / cm 3 Example 2 Suspension stabilizer was added at 2%, and the upper and lower density difference of cement paste was 0 after standing at 93°C for 2h, and the upper and lower density difference of cement paste was 0.024g / cm after standing at 180°C for 24h. 3 Example 3 Suspension stabilizer was added at 2%, and the upper and lower density difference of cement slurry was 0 after standing at 93°C for 2h, and the upper and lower density difference of cement stone was 0.014g / cm after standing at 180°C for 24h. 3 ; The free liquid in each embodiment is 0.

[0113] On the basis that various properties meet the requirements of cementing construction, the mechanical properties of the high-temperature resistant, high-strength, low-density cement slurry in the present invention are evaluated. As can be seen from Table 1, the high-temperature, high-strength, low-density cement slurry prepared based on glaze-sealed hollow glass microspheres has an increased compressive strength under high-temperature conditions with the extension of the curing time; under the same curing conditions, the compressive strength increases with the increase of the cement slurry density. The glaze-sealed hollow glass microspheres (A) used in Example 1 contain 40.5 parts of hollow glass microspheres, 3.3 parts of silane coupling agents, 10.8 parts of active monomers containing chelating groups, and 44.8 parts of glaze-sealed materials. After mixing them according to 100 parts of oil well cement, 60 parts of glaze-sealed hollow glass microspheres (A), 15 parts of high-temperature strength anti-decay materials, 4 parts of high-temperature anti-cracking materials, 2 parts of dispersants, 3 parts of second suspension stabilizers, 5 parts of high-temperature water loss reducers, 2 parts of high-temperature retarders, 1 part of defoaming agents, and 80 parts of tap water, the obtained cement slurry density is 1.30g / cm 3 , the compressive strength at 180℃ for 24h is 17.3MPa, and 48h is 20.1MPa, which is an increase of 16.2%. The glaze sealing hollow glass microspheres (B) used in Example 2 contain 38.5 parts of hollow glass microspheres, 3.1 parts of silane coupling agent, 10.8 parts of active monomers containing chelating groups, and 46.5 parts of glaze sealing materials. After mixing them according to 100 parts of oil well cement, 40 parts of surface-modified hollow glass microspheres (B), 15 parts of high-temperature strength anti-decay material, 4 parts of high-temperature anti-cracking material, 1.5 parts of dispersant, 2 parts of second suspension stabilizer, 5 parts of high-temperature fluid loss agent, 2.2 parts of high-temperature retarder, 1 part of defoaming agent, and 73 parts of tap water, the obtained cement slurry density is 1.40g / cm 3 The compressive strength is 19.6MPa after curing at 180℃ for 24h and reaches 23.3MPa after 48h.

[0114] In the above embodiments, the glaze-sealed hollow glass microspheres have a high applicable temperature, are less affected by the high pH environment generated by cement hydration under high temperature conditions, and have a strong bonding ability with silicate oil well cement during the high temperature curing process of cement slurry, reducing the risk of cracks and defects between the microspheres and the cement matrix. After being mixed with oil well cement, admixtures, and additives to form a high temperature, high strength, and low density cement slurry, the high temperature strength anti-decay material composed of composite silicon micropowder and crystalline silicon micropowder can not only optimize the silicon-calcium ratio (Si / Ca) of the cement slurry system, adjust cement hydration products, and prevent the decline of cement matrix strength, but also achieve the close stacking of solid phase particles in the cement slurry, ensuring the high temperature compressive strength of cement stone. In the high-temperature anti-cracking material composed of inorganic short fibers and styrene-butadiene rubber powder, the inorganic short fibers have strong temperature resistance and can be inserted into cement particles and hydration products, playing a "tensioning" role to inhibit the high-temperature deformation of the cement matrix; the polymer styrene-butadiene rubber powder has strong deformation ability under high-temperature conditions and has certain adhesion. It can fill a layer of flexible polymer film between cement particles or between cement particles and glaze-sealed hollow glass beads to reduce the damage of cement stone caused by external mechanical shock or thermal shock.

[0115] Commercially available hollow glass microspheres were used as comparative examples. Under the same experimental conditions, the thickening time of comparative example 1 was 325 min ( Figure 4 ), water loss Q 30 The density difference of cement slurry after standing at 93℃ for 2h is 0.06g / cm 3 , free liquid 0.36%; compared with Example 1, the water loss Q 30 The increase was 14mL, and the rheological properties were not much different. The compressive strength after curing at 180℃ for 24h decreased by 56.6%, and the compressive strength after 48h decreased by 71.1%, respectively, which showed obvious attenuation. Compared with Example 2, the thickening time of Comparative Example 2 was extended by 23min, and the water loss Q 30 The increase of 12mL, the compressive strength of 24h and 48h under 180℃ curing conditions decreased by 48.5% and 63.1% respectively, and the strength was attenuated; at the same time, free liquid appeared during the standing of the cement slurry. Compared with Example 3, the thickening time of Comparative Example 3 was extended by 5min, and the water loss Q 30 With an increase of 6 mL, the compressive strength at 180°C for 24h and 48h decreased by 35.5% and 57.9%, respectively. The above experimental data show that the low-density cement slurry prepared with unmodified commercial hollow glass microspheres has low compressive strength at 180°C and there is obvious attenuation.

[0116] The experimental results show that under the same density conditions, surface glaze treatment is beneficial to improving the micro-beads' resistance to high-alkalinity corrosion under high-temperature conditions, enhancing the physical filling between the micro-beads and the cement matrix, inhibiting the generation of micro-cracks, thereby improving the compressive strength of low-density cement slurry, and at the same time, it also has a positive effect on controlling water loss and improving sedimentation stability.

[0117] Therefore, the surface glaze-sealed glass microspheres provided by the present invention and the high-temperature, high-strength, low-density cement slurry prepared based on the surface glaze-sealed glass microspheres can obtain an adjustable density (1.30-1.50 g / cm 3 ), with low water loss, good sedimentation and fluidity, it is a high-performance low-density cementing working fluid that can meet the needs of cementing and cementing construction; at the same time, it has high compressive strength and no attenuation under high temperature conditions of 180°C. This cement slurry provides strong technical support for cementing operations in complex deep and ultra-deep wells with low formation pressure bearing capacity, narrow safety density window, and high requirements for production layer protection.

[0118] In embodiments 1 to 3 of the present invention, hollow glass microspheres with surface glaze are used as lightening agents, and the density of cement slurry is adjusted by utilizing the hollow and low-density characteristics thereof; molecular chains rich in adsorption groups (-COOH) are grafted onto the surface of hollow glass microspheres by utilizing silane coupling agents, and the adhesion effect of glaze slurry on the surface of hollow glass microspheres is improved through the adsorption and chelation between -COOH and heavy metal ions in nano inorganic mineral powder; small molecule organic acid salts are used as auxiliary agents to assist the uniform coating and deep penetration of glaze slurry materials on the surface of hollow glass microspheres. On this basis, by variable temperature continuous drying, cracking of glaze slurry on the surface of hollow glass microspheres due to rapid escape of water or uneven escape rate is avoided; and by low temperature firing, hollow glass microspheres with a layer of heat-resistant and corrosion-resistant enamel layer on the surface are finally obtained, thereby improving its macroscopic mechanical properties and the ability to resist corrosion by cement hydration products, formation fluids, etc., and improving the structural integrity and compressive strength of low-density cement stone under high-temperature working conditions at the bottom of the well.

[0119] High-temperature strength anti-decay materials are composed of different types of silica powder. On the one hand, the small particle size and good workability are used to improve the particle grading of the system, physically fill the capillary channels and microcracks in the cement slurry system, and achieve a denser stacking; on the other hand, by adjusting the silicon-calcium ratio (Si / Ca) of the cement slurry system and optimizing the hydration products, the development defects of cement stone under high temperature conditions are compensated, the micro and submicro structures of cement stone are improved, and the mechanical properties are improved.

[0120] The whiskers and short fibers in the high-temperature anti-cracking material can be inserted into the cement particles and hydration products, or aggregate and overlap on the interstitial surfaces of these materials to form a skeleton structure, which plays the role of "stretching" and toughening, and inhibits the high-temperature deformation of the cement matrix; the styrene-butadiene rubber powder has good thermal stability, certain flexibility and adhesion, and can be filled between cement particles or between cement particles and hollow glass microspheres sealed on the surface to form a polymer network, reducing the damage of cement stone caused by external mechanical shock or thermal shock. At the same time, the presence of whiskers can also provide a condensation center for the formation of early hydration products of cement, promote the crystallization nucleation and growth of hydration products, and accelerate the cement hydration process and the development of early strength.

[0121] Other admixtures used in high-temperature, high-strength, low-density cement slurry, such as high-temperature retarders, high-temperature fluid loss reducers, suspension stabilizers, dispersants and defoamers, are all mature products. The relevant mechanisms and properties are well known to those skilled in the art and will not be elaborated on.

[0122] The high temperature, high strength and low density cement slurry prepared in Examples 1 to 3 of the present invention has an adjustable density (1.30 to 1.50 g / cm 3 ), 180℃ high temperature 24h compressive strength greater than 18MPa, 48h compressive strength greater than 25MPa, low API water loss, good rheological properties, free liquid is 0, density difference less than 0.05g / cm 3 It provides strong technical support to reduce the risk of leakage during cementing construction and ensure the exploration and development benefits of difficult-to-use reserves and unconventional oil and gas resources in complex deep wells and ultra-deep wells.

[0123] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing hollow glass microspheres with surface glaze, characterized in that: The raw material composition of the surface glaze sealing hollow glass microspheres includes, by weight: 36.5-40.5 parts of hollow glass microspheres, 2.9-3.3 parts of silane coupling agents, 9.2-11 parts of active monomers containing chelating groups, 44.8-50.3 parts of nano-scale glaze sealing materials, 0.9-1 parts of auxiliary agents, and 1.3-1.5 parts of first suspension stabilizers; The preparation method comprises: The hollow glass microspheres are added into an anhydrous ethanol solution, and a silane coupling agent is added dropwise, and the solution is separated, rinsed, and dried to obtain hollow glass microspheres with the silane coupling agent grafted on the surface; The hollow glass microspheres with silane coupling agent grafted on the surface and the active monomer containing chelate group are added into deionized water for mixing, an initiator is added for reaction, an inhibitor is added, and the hollow glass microspheres with chelate group grafted on the surface are prepared after washing and drying; Adding the first suspension stabilizer, the nano-scale glaze sealing material and the auxiliary agent into deionized water, and stirring evenly to prepare a glaze sealing slurry; The hollow glass microbeads with chelating groups grafted on the surface are sprayed with glaze slurry, vacuum dried and fired to obtain the hollow glass microbeads with glaze sealing on the surface.

2. The method according to claim 1, characterized in that The compressive strength of the hollow glass microspheres is 12000 psi.

3. The method according to claim 1, characterized in that The silane coupling agent is γ-methacryloxypropyltrimethoxysilane.

4. The method according to claim 1, characterized in that: The active monomer containing a chelating group is itaconic acid and / or fumaric acid.

5. The method according to claim 1, characterized in that The nano-grade glaze sealing material comprises, by weight, 16.7 to 33.3 parts of 300 to 500 nm nano-dolomite, 25 to 33.3 parts of 100 to 500 nm nano-zircon powder, 15.4 to 33.3 parts of 400 to 1000 nm nano-sodium potassium stone powder, and 16.7 to 23.1 parts of 50 to 300 nm nano-strontium carbonate powder.

6. The method according to claim 1, characterized in that The auxiliary agent is at least one of the following: sodium tripolyphosphate, sodium tetraphosphate, and sodium tannate.

7. The method according to claim 1, characterized in that The first suspension stabilizer is bentonite and / or china clay.

8. The method according to any one of claims 1 to 7, characterized in that: The preparation method specifically comprises: The hollow glass microspheres are added to an anhydrous ethanol solution, and a silane coupling agent is added dropwise at 60 to 70° C. within 1 hour; then cooled to room temperature, separated by a high-speed centrifuge, and the separated product is washed with deionized water until it is neutral, and dried to obtain hollow glass microspheres with a silane coupling agent grafted on the surface; The hollow glass microspheres with surface grafted silane coupling agent and active monomers containing chelating groups are added to deionized water, mixed, stirred evenly, adjusted to a neutral pH value, and supplemented with deionized water to make the solid content in the suspension reach 15wt%; a protective gas is introduced, the temperature is raised to 50°C, an initiator is added to react, and the reaction is stirred for 6 to 8 hours at a temperature preservation temperature; the protective gas is turned off, an inhibitor is added, stirred, cooled to room temperature, washed with clean water, and spray-dried to obtain hollow glass microspheres with surface grafted chelating groups; The first suspension stabilizer, the nano-scale glaze sealing material and the auxiliary agent are added into deionized water, the deionized water is supplemented so that the content of the nano-scale glaze sealing material in the suspension reaches 70wt%, and the glaze sealing slurry is prepared by stirring evenly; The sealing glaze slurry is sprayed evenly onto the hollow glass microspheres with chelating groups grafted on the surface by a spraying method; dried in a vacuum oven at 60°C for 1 day, dried at 110°C for 2 days, and sieved; fired in a high-temperature electric furnace at 800-1200°C for 8-10 hours, cooled and sieved to obtain a powder material as the surface glaze sealing hollow glass microspheres.

9. A hollow glass microsphere with surface glaze, characterized in that: The hollow glass microspheres are prepared by the method for preparing hollow glass microspheres with surface glaze according to any one of claims 1 to 8.

10. A high-temperature, high-strength, low-density cement slurry, characterized in that: The raw material composition of the high-strength and low-density cement slurry includes, by mass, 100 parts of G-grade oil well cement, 29-60 parts of the surface glaze hollow glass microspheres described in claim 9, 15 parts of high-temperature strength decay material, 4 parts of high-temperature anti-cracking material, 2-3 parts of a second suspension stabilizer, 1.2-2 parts of a dispersant, 4.3-5 parts of a high-temperature fluid loss reducer, 2-2.5 parts of a high-temperature retarder, 1 part of a defoaming agent, and 67-80 parts of tap water.

11. The high temperature, high strength and low density cement slurry according to claim 10, characterized in that: The high temperature strength decay material is prepared by compounding 325 mesh composite silicon micropowder and 1500 mesh crystalline silicon micropowder in a mass ratio of 5:

1.

12. The high temperature, high strength and low density cement slurry according to claim 10 or 11, characterized in that: The high-temperature anti-cracking material comprises, by weight, 10 parts of 1-3 mm calcium sulfate whiskers, 30 parts of 2-4 mm basalt fibers, 20 parts of 1-3 mm aluminum oxide whiskers, and 40 parts of styrene-butadiene rubber powder.

13. Use of the high temperature, high strength and low density cement slurry according to any one of claims 10 to 12 in well completion and cementing.

Citation Information

Patent Citations

  • A strong inhibitory retarder for medium and high temperature oil well cement and its preparation method

    CN106008844B

  • Suspended stable fluid loss agent, preparation method thereof and application of fluid loss agent in horizontal well cementation

    CN113336896A

  • Weak gelling agent, preparation method of weak gelling agent, cement paste suspension stabilizer and application of cement paste suspension stabilizer

    CN114716605A

  • Low-density cement paste system

    CN104178096A

  • Hollow glass beads and application thereof

    CN106517804A